Utwory osierocone jako zagadnienie prawa i kultury - Jarmuszkiewicz, Anna (Tematy i Konteksty, 2017)
The article presents contemporary definitions of orphan works, the problems associated with these definitions and the importance of the existence of orphan works for contemporary culture in the context of cultural memory.